Regional spatial variability of soil organic carbon in 0–5 m depth and its dominant factors - Zhou, Jingxiong; Wang, Yunqiang; Tong, Yongping; Sun, Hui; Zhao, Yali; Zhang, Pingping (Catena (Giessen), 2023)
[Display omitted] •A critical depth was detected (180 cm), above which SOC differed significantly among land uses.•Low SOC content in the central area of the northern Chinese Loess Plateau corresponded to the aeolian sand area of Ordos.•Soil texture and temperature controlled SOC throughout the 0–500 cm soil profile.•The spatial variations and forcing factors of SOC were all depth-dependent. Soil organic carbon (SOC) stored in deeper soils is becoming increasingly significant in carbon management and carbon cycle especially in the face of climate and land use alterations. However, spatial variability of deep SOC at a regional scale and its related dominant factors are rarely investigated. To ascertain the vertical distribution and regional spatial variations in the SOC content of deep soil, 1648 soil samples were collected from 67 sites across the Chinese Loess Plateau (CLP) at a depth of 500 cm. Results showed that the mean SOC content of three land use types were recorded as follows: cropland (2.93 ± 0.29 g kg−1) > forest (2.56 ± 0.24 g kg−1) > grassland (2.39 ± 0.29 g kg−1), and the vertical distribution of soil profile from 0 to 500 cm was similar. Furthermore, a significant alteration in SOC content was observed in the soil layer of 0–180 cm among the three land use types (p < 0.05). Spatial distribution maps of SOC content indicated that there was a central region of the northern CLP with low SOC content, which corresponds to the eolian sand area in Ordos. Both the spatial variations and influencing factors of SOC content were found to be depth-dependent, but soil texture and temperature were identified as the dominant factors affecting the 0–500 cm soil profile of the CLP. Clarifying this information is helpful for understanding content level and variation of deep SOC, which can provide a reference for carbon sequestration in deep soil and developing sustainable SOC management for the CLP and other related ecological regions.